The Mediating Role of Energy Use as Impact of Renewable Energy, Urbanization, Industrialization, and Economic growth on Co2 Emissions in Developing Asian Countries. - Rana Sharjeel Akhtar; Samar Abbas; Inaya Sari Melati (Journal of Economic Education, 2026)
This study presents the dynamic impact of renewable energy consumption, urbanization, industrialization and economic growth on CO₂ emissions in developing Asian countries. Energy use demonstrated as a mediating factor and using a balanced panel model in Pakistan, India, Bangladesh, Indonesia, Sri Lanka, Vietnam, Kyrgyzstan and the Philippines countries over the 2000-2024. These analysis data collection on World Development Indicators WDI database and engagement panel regression methods under a pooled least squares framework. The empirical results are demonstration that renewable energy use, urbanization, industrialization and GDP use statistically significant effects on CO₂ emissions and the aggregate energy use increase as a strong and significant mediator linking these drivers to environmental results. The positive implication between renewable energy and CO₂ emissions suggests that is the current penetration levels and renewables may be complementing rather than relieving the fossil fuel use, especially in fast urbanizing and industrializing economies. These findings underscore the need for policies that not only expand renewable capacity but also fast-track fossil fuel movement and improve energy efficiency. The study highlights the importance of sectoral and source specific energy evolutions to achieve effective decoupling of economic growth from carbon emissions in developing Asia.